Perceived Risk of Infection Linked to Changes in Comfort in Social Situations From Before to During the COVID-19 Pandemic - Stierand, Janine; Luebber, Finn; Krach, Sören; Paulus, Frieder Michel; Rademacher, Lena (Frontiers in Psychiatry, 2021)
Background: Social lives have significantly changed since social distancing measures have been implemented to prevent the spread of the coronavirus disease 2019 (COVID-19). This study aimed to investigate how our appraisal of social situations changed during the pandemic. Methods: In two online surveys, conducted in October 2019 and April 2020, 58 participants rated their personal level of comfort for sketches depicting social situations. Situations were separately categorized according to the risk of a possible COVID-19 infection and changes in ratings were analyzed by using a repeated measures ANOVA. Moreover, potential influencing factors on the change in ratings such as perceived infection risk and social factors like regular frequency and liking of social interactions were examined. Results: There was a significant interaction (p < .001) between time of measurement and risk category. Comfort ratings of depicted situations with low and medium infection risk were higher during the second compared to the first survey period. Ratings of high-risk situations did not change significantly, although there was a tendency towards lower ratings during the pandemic. Multiple regression analyses showed that perceived probability of short-term infection could explain variance in the change of ratings of social situations with low- and medium risk, but not perceived probability of long-term infection or social factors. Conclusion: The results suggest that the change of participant’s appraisal of the social situations during the COVID-19 pandemic relates to perceived infection risk. Both, the risk associated with the specific scenario as well as the general belief of short-term infection risk were associated with change. This change predominantly manifested in greater thought of comfort during low and medium risk situations, which might give a sense of safety during the pandemic. The finding that high-risk social situations were not rated as uncomfortable as expected must be considered with regard to the young sample and may not be generalizable to other individuals. Further research is necessary to evaluate long-term effects on social interactions caused by global pandemics such as the COVID-19 pandemic.